Bibliometric Analysis Of High-Rise Building Planning With Cpm And Pert Methods Using Vosviewer - Daniel Arnoldi Gultom; Andri Irfan Rifai; Mulia Pamadi; Muhammad Isradi (Journal Of Social Science (JoSS), 2024)
This research shows the developments that have occurred in high-rise building building planning worldwide by presenting bibliometric analysis data. The database that appears from Publish or Perish can be converted into mapping with the help of VosViewer software. In this analysis, it can be seen how relevant this research is globally. The results of data processing show that the majority of research comes from journal articles, with a total of 774 studies (85.33%), and the peak of research occurred in 2022 with 114 studies. Elsevier BV is a publisher that has a high interest in the development of high-rise building planning, with a total of 432 studies (65.90%). Evaluation is the most dense visualization, followed by buildings and high-rise buildings. This shows that high-level building planning using the CPM and PERT methods can still develop.